Histopathologic Review of Previously Negative Prostatic Core Needle Biopsies following a New Diagnosis of Adenocarcinoma of the Prostate by Core Needle Biopsies: Implications for Quality Assurance Programs - Jay Patel; Lester J. Layfield M.D (SAGE Publishing, 2008)
Programs for quality assurance are increasingly important in surgical pathology. Many quality assurance (QA) techniques for surgical pathology were adopted from procedures introduced in cytopathology. Surgical pathology specimens have diminished in size such that the majority of diagnostic biopsies of prostatic lesions are now core needle biopsies. These specimens raise issues similar to those of cytology specimens, including concerns regarding adequacy and the representative nature of the biopsy. Due to sample size, some neoplasms may not be diagnosed on initial biopsy, raising concerns regarding false negative results. Cytopathologists have instituted QA procedures including review of all previously negative slides received within five years prior to the new diagnosis of high grade squamous intraepithelial lesion or gynecologic malignancy. No such requirement exists in surgical pathology for review of core biopsies. The Department of Pathology at the University of Utah instituted a QA policy requiring review of prior negative prostatic needle biopsies following a new diagnosis of prostatic adenocarcinoma. We reviewed five years of QA records of prostate needle biopsy review. During this time, nine hundred and fifty-eight core biopsy sets were performed. Two hundred and ninety-five of these contained at least one biopsy with a diagnosis of adenocarcinoma. Two hundred and eight patients had a prior set of prostatic needle biopsies with a diagnosis of adenocarcinoma. The remaining 87 had prior biopsies with either a diagnosis of prostatic intraepithelial neoplasia (23), small atypical acinar proliferation (21) or no evidence of malignancy (43). QA review of these 87 cases revealed two biopsies which revealed foci of adenocarcinoma. Both had been initially diagnosed as no evidence of malignancy. The false negative rate for core biopsy was 0.68%. In an additional twenty-one cases, microscopic foci of atypical small acinar proliferations were found in core biopsies antedating the positive core biopsy (7.1%).